Implementasi Media Quizizz dalam Meningkatkan Keterampilan Membaca Bahasa Arab Siswa - Rahmawati, Nur Laila; Asnawi, Asnawi; Anas, Malikul; Sa’adah, Diva Nur; Faridaturrohmah, Faridaturrohmah (TARBAWIYAT, 2025)
The purpose of this study is to describe the implementation and effectiveness of Quizizz as a medium to improve Arabic reading skills (maharah al-qira'ah) in children. This reading skill includes the ability to read Arabic text fluently, translate it, and understand it properly and correctly. Reading skills play a crucial role in understanding written information. An innovative way to enhance this skill is by using interactive learning media such as Quizizz. This research employed a descriptive qualitative method. The findings indicate that the use of Quizizz—through formats like images, story sentences, and dialogues—can effectively improve children's reading skills. Learning activities become more dynamic, making children highly engaged, active, cheerful, and motivated to learn and read Arabic texts.